Stamp taxes 2020/21 - Wright, Ken (London [England] : bBloomsbury Professional, 2020)
"Stamp Taxes 2020/21 is a comprehensive and practical guide to all current UK stamp and land taxes: Stamp Duty Land Tax (England and Northern Ireland), Stamp Duty (UK) and Stamp Duty Reserve Tax (UK), together with commentary on Land and Buildings Transaction Tax (Scotland) and Land Transaction Tax (Wales). It explains the reasons behind many of the current rules by exploring the history and development of stamp taxes, whilst setting out the scope of each tax and explaining how they interact. This new edition includes the following: - Analysis of the provisions of Finance Act 2020 (Finance Bill 2019-2021) as follows: (a) Market value rule for both stamp duty and SDRT purposes on the transfer of unlisted shares and securities to a connected company for consideration all or part of which comprises an issue of shares (b) Exclusion of 'partition demergers' from the meaning of 'disqualifying arrangements' for the purposes of FA 1986, s 77A provided certain conditions are satisfied - Consideration of the Government's proposal to charge a 2% surcharge on top of existing SDLT rates for purchases of residential property by non-UK residents from 1 April 2021 - Commentary on updated HMRC guidance as to the meaning of (a) 'residential property' and (b) 'garden or grounds' of a dwelling, for SDLT purposes. The commentary includes consideration of the latest case law on these matters - Analysis of the updated HMRC guidance on the application of the SDLT anti-avoidance provision in FA 2003, ss 75A ? 75C and the recent case law relating to that anti-avoidance provision - Details of HMRC's revised procedures for SDLT, stamp duty and SDRT as a result of the Covid-19 pandemic - A summary of the temporary changes made to the SDLT, LTT and LBTT rates and bands for residential property by the UK, Welsh and Scottish governments Including numerous examples, with references to legislation, case law and HMRC guidance throughout, this is a practical handbook for those working in tax advisory firms and tax departments of corporate groups and other major investors in UK property and companies. It is also a useful study aid for students and trainees studying for membership of professional bodies."--
Chapter 1 Introduction to Stamp Taxes -- Chapter 2 Scotland - Land and Buildings Transaction Tax -- Chapter 3 Wales - Land Transaction Tax -- Chapter 4 SDLT - General Rules -- Chapter 5 SDLT Reliefs -- Chapter 7 SDLT and Partnerships -- Chapter 8 SDLT Administration and Compliance -- Chapter 9 SDLT Anti-Avoidance Rules -- Chapter 10 Stamp Duty - General Rules -- Chapter 11 Stamp Duty Reliefs -- Chapter 12 Stamp Duty Reserve Tax (SDRT) -- Chapter 13 Planning, Pitfalls and Legacy Liabilities -- Appendix A Addresses, Contact Details, etc -- Appendix B Sample Forms, etc -- Appendix C Stamp Taxes - HMRC Revised Procedures as a Result of Covid-19 (Coronavirus)
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Stamp duties -- Great Britain; Taxation; Electronic books